Vascular Tone and Neurovascular Coupling: Considerations Toward an Improved In Vitro Model - Filosa, Jessica (Frontiers in Neuroenergetics, 2010)
Neurovascular research has made significant strides toward understanding how the brain neurovascular unit accomplishes rapid and spatial increases in blood flow following neuronal activation. Among the experimental models used, the in vitro brain slice preparation provides unique information revealing the potential signals and cellular mechanisms involved in functional hyperemia. The most crucial limitation of this model, however, is the lack of intraluminal pressure and flow in the vessels being studied. Moreover, differences in basal vascular tone have led to varied interpretations regarding the polarity of vascular responses following neuron-to-glial stimulation. Given the complexity of astrocyte-induced neurovascular responses, we propose the use of a modified in vitro brain slice preparation, where intraluminal arteriolar pressure and flow are retained. Throughout this review, we discuss the advantages and disadvantages to be considered when using brain slices for neurovascular studies. Potential ways to overcome the current limitations are proposed.